A lumped parameter modelling method for high-temerature geothermal reservoirs - Björn Sveinbjörnsson (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri High-temperature geothermal resources, which are those that are exploited for producing electricity, have been thoroughly studied using a variety of techniques. They have been modeled conceptually and numerically, using programs such as iTOUGH2. There has not been much effort placed on using more simple techniques, such as lumped parameter methods. This is due to the necessity of dealing with temperature effects, and up to date, lumped parameter methods have been mostly limited to models incorporating only pressure changes. Here a method has been developed which accommodates both pressure and temperature/enthalpy data. A one and two-tank model has been elaborated. The model has been tested against user generated data as well as data from Krafla and Bjarnarflag geothermal power stations. The model was found to match the data in some cases, with the 1-tank model matching the data more closely. The results show the possibility of using the model as a part of the management of high temperature geothermal reservoirs.